Landscape metrics applied in geomorphology: hierarchy and morphometric classes of sand dunes in Inner Somogy, Hungary - Györgyövics, Katalin; Kiss, Tímea (Hungarian Geographical Bulletin, 2016)
Landscape metric is mostly used to quantify landscape patches. However, these patches could also be geomorphological forms, thus using traditional landscape metrics their shape and spatial distribution, or their dynamics could be analysed. The aim of the paper is to study the geomorphological applicability of different indices studying the aeolian forms of Inner Somogy (SW Hungary). In the present research 15 landscape metric indices were calculated with Patch Analyst 5.1 and vLATE 2.0. The negative aeolian forms (blowout depressions and holes) have high number but small size, whilst the positive forms (parabolic dunes and hummocks) have large number and complex spatial structure, thus the negative and positive forms can not be directly connected. The spatial distribution revealed by the applied indices refers to differences in moisture content, abundance of sand supply and relief on a regional scale. The negative forms appear in a considerable distance from each other, while the positive forms tend to cluster. Based on the spatial distribution of the forms the matrix could be described as an erosion-transportation zone, and in three accumulation zones the dune size and superimposition increases downwind.